FAKTOR PENYEBAB PERILAKU SOSIAL YANG MENYIMPANG PADA USIA REMAJA SERTA PERAN ORANG TUA - Rizki Dewi Astriani (UNIVERSITAS PGRI TULUNGAGUNG, 2023)
Education is obtained from the school environment. In addition to academic education, students also receive education to behave in accordance with regulations. However, not all students obey the rules that have been set. Even instant culture has entered the world of adolescents, such as lazy learning patterns, aspiring but refusing to try, free association, and dating which results in reduced learning focus. Adolescence is a time when children reach adulthood. Not a few teenagers who commit crimes that cause anxiety in their parents and social environment unrest so that it can be called deviant action. Deviation is behavior that is far from the values and norms that apply to society. Forms of deviant behavior by teenagers include fighting, sex outside marriage, drug abuse, and beatings. This research was conducted to find out what factors are the causes of deviations committed by adolescents. Namely internal factors and external factors. And knowing the role of parents in providing a good role model for their teenagers. The research method used is a qualitative method by means of triangulation, the technique used is purposive and inductive data analysis.Keyword: education, deviance, adolescence.